Effect of Gum Arabic on Hematological Parameters in Alloxan-induced Diabetic Mice - Mahmoud Elderbi,; Ashref Elburi,; Arwa Ibrahim,; Muatasembellah Buzreiba, (AlQalam Journal of Medical and Applied Sciences, 2026)
This study evaluated the antihyperglycemic effects of gum arabic (GA) and its impact on hematological parameters in alloxan-induced diabetic mice. Swiss albino mice (n=40) were divided into normal control (C),10% GA-treated only group (GA), diabetic Alloxan-induced diabetic group (AX), and alloxan and GA-treated group (AXGA). Diabetes was induced via intraperitoneal alloxan (200 mg/kg), justified by established protocols for reproducible hyperglycemia. Body weight, fasting blood glucose (FBG), and hematological indices (White blood cells, red blood Cells and platelet indices) were assessed over 30 days. Data were analyzed using one-way ANOVA with a significance value of p<0.05. Alloxan-treated mice cause a dramatic increase in FBG to 436±37.55mg/dl vs 130.00±7.74mg/dl in control mice (p<0.05). The FBG in GA-treated mice was increased to 156.67±8.04mg/dl, but was insignificant compared to the control. However, GA treatment in diabetic mice(AX+GA) significantly reduced FBG to 146±10.01mg/dl compared to untreated diabetic mice and restored body weight compared to the AX group. Hematological changes included reduced WBC Number and lymphocyte percentages (to 5.22×103 /µL and 51.7% compared with control, respectively) and lowered Hb (11.5±0.8 vs. 13.2±1.0 g/dL in C, p<0.05). Gum Arabic demonstrates significant antihyperglycemic effects in alloxan-induced diabetic mice. It also exhibits modulatory effects on hematological parameters, suggesting potential anti-inflammatory properties. These findings support the traditional use of GA and highlight its potential as an adjunct therapy for diabetes management.